Política, justicia, educación - Manuel-Reyes Mate (Theoría Revista del Colegio de Filosofía, 2002)
This essay deals with one basic question: ¿how to educate in politics and justice, conceiving them not as politicization but as a responsible exercise of the human being that does not renounce to reason nor to moral in the construction of public life? In order to answer this question I analyze, in the first place, the modern conception of policy, justice and education and, in the second place, I propose another way of understanding them jointly.